Comparative conventional- and quantum dot-labeling strategies for LPS binding site detection in Arabidopsis thaliana mesophyll protoplasts - Mgcina, Londiwe S.; Dubery, Ian A.; Piater, Lizelle A. (Frontiers in Plant Science, 2015)
Lipopolysaccharide (LPS) from Gram-negative bacteria is recognized as a microbe-associated molecular pattern (MAMP) and not only induces an innate immune response in plants, but also stimulates the development of characteristic defense responses. However, identification and characterization of a cell surface LPS-receptor/binding site, as described in mammals, remains elusive in plants. As an amphiphilic, macromolecular lipoglycan, intact LPS potentially contains three MAMP-active regions, represented by the O-polysaccharide chain, the core and the lipid A. Binding site studies with intact labelled LPS were conducted in Arabidopsis thaliana protoplasts and quantified using flow cytometry fluorescence changes. Qdots, which allow non-covalent, hydrophobic labelling were used as a novel strategy in this study and compared to covalent, hydrophilic labelling with Alexa 488. Affinity for LPS-binding sites was clearly demonstrated by concentration-, temperature- and time-dependent increases in protoplast fluorescence following treatment with the labelled LPS. Moreover, this induced fluorescence increase was convincingly reduced following pre-treatment with excess unlabeled LPS, thereby indicating reversibility of LPS binding. Inhibition of the binding process is also reported using endo- and exocytosis inhibitors. Here, we present evidence for the anticipated presence of LPS-specific binding sites in Arabidopsis protoplasts, and furthermore propose Qdots as a more sensitive LPS-labelling strategy in comparison to the conventional Alexa 488 hydrazide label for binding studies.